Precompetition medical assessment of referees and assistant referees selected for the 2010 FIFA World Cup. Issue 5 (5th December 2011) - Bizzini, Mario; Schmied, Christian; Junge, Astrid; Dvorak, Jiri
Abstract : Background: Several proposals for preparticipation screening to detect risk factors for sudden cardiac death in sports have been published, but referees have been neglected in this respect. Methods: A standardised precompetition medical assessment (comprising a general physical, orthopaedic and cardiac examination and blood analysis) was performed in all 90 referees and assistant referees selected for the 2010 Fédération Internationale de Football Association World Cup. Results: More than a third of the referees showed at least one pathological finding in cardiac examinations; however, all follow-up examinations proved to be normal. The relatively high prevalence of pathological findings in the blood analysis and the orthopaedic examination can be attributed to the average age of the referees and none of them was performance limiting. Conclusions: Considering their risk of occult ischaemic heart disease, a precompetition medical assessment including an exercise ECG is recommended in elite male football referees.